2020
DOI: 10.1155/2020/5162350
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacytidine-Induced Cardiomyocyte Differentiation of Very Small Embryonic-Like Stem Cells

Abstract: The use of stem cells in generating cell-based pacemaker therapies for bradyarrhythmia is currently being considered. Due to the propensity of stem cells to form tumors, as well as ethical issues surrounding their use, the seed cells used in cardiac biological pacemakers have limitations. Very small embryonic-like stem cells (VSELs) are a unique and rare adult stem cell population, which have the same structural, genetic, biochemical, and functional characteristics as embryonic stem cells without the ethical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…5-AzaC, a demethylating drug, mainly binds to DNA methyltransferase through covalent bonds to form an irreversible complex, which reduces the level of genomic methylation and reactivates hypermethylated tumour suppressor genes. At present, many studies have confirmed that most of the CpG islands in the promoter region of many tumour suppressor genes are in a state of hypermethylation, and the expression of protein can be restored after intervention with the demethylated drug 5-AzaC (Sun et al 2020 ). Additionally, it has been reported that zebularine can activate the tumor suppressor genes p15 , p16 , and p57 by demethylation in gastric cancer cells (Pan et al 2016 ).…”
Section: Treatmentmentioning
confidence: 99%
“…5-AzaC, a demethylating drug, mainly binds to DNA methyltransferase through covalent bonds to form an irreversible complex, which reduces the level of genomic methylation and reactivates hypermethylated tumour suppressor genes. At present, many studies have confirmed that most of the CpG islands in the promoter region of many tumour suppressor genes are in a state of hypermethylation, and the expression of protein can be restored after intervention with the demethylated drug 5-AzaC (Sun et al 2020 ). Additionally, it has been reported that zebularine can activate the tumor suppressor genes p15 , p16 , and p57 by demethylation in gastric cancer cells (Pan et al 2016 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Currently, the efficiency of stem cell induction into cardiomyocytes is low, which limits its clinical application. Our previous study treated very small embryonic-like stem cells with 5-AZA and the positive expression rates of cTnT and α-actin were 18.41 and 19.43%, respectively on day 14 (19). In the present study, epigenetics was used to improve the differentiation efficiency of stem cells.…”
Section: Discussionmentioning
confidence: 72%
“…There are some differences between these two kinds of cells in terms of extraction methods, culture conditions and morphological characteristics. The morphological changes during induction differentiation were not identical [27,28].…”
Section: Discussionmentioning
confidence: 91%
“…The mechanism of 5-AZA may be related to CpG base-pair demethylation and regulation of early myocardial transcription factors [32,33]. Currently, the efficiency of stem cell induction into cardiomyocytes is low, which limits its clinical application [34]. In the present study, epigenetics was used to improve the differentiation efficiency of stem cells.…”
Section: Discussionmentioning
confidence: 92%